The Art of Luxury: Sealy Brand Personality Identification - Rudy Prilto Lesmana; Margaretha Margawati van Eymeren; Ferdinand Fransiscus Tanuwidjaja (Sekolah Tinggi Manajemen IPMI, 2021)
Sealy is one of luxury mattress brands in the global market that since 2013 strives to have a successful business in the Indonesia luxury mattress market. In Indonesia, Sealy competes directly with many top collection models from several other international mattress brands. To face the competition, Sealy needs brand personality. This research aims to identify Sealy's brand personality, which can be used as a guideline for the company when setting up its marketing communication plan. This research's methods are qualitative, and as desk research, the unit analysis are both product-related and non-product-related characteristics of Sealy that called drivers. This research constructs a category based on 42 traits, 15 facets, and 5 dimensions of Aaker’s brand personality framework to analyze Sealy's specific brand drivers. The result is that Sealy main personalities are leader and upper class from competence and sophistication dimensions.